2019
DOI: 10.31788/rjc.2019.1225126
|View full text |Cite
|
Sign up to set email alerts
|

PREPARATION AND CHARACTERIZATION OF ANTIBACTERIAL FILM BASED ON CARBOXYMETHYLCELLULOSE FROM GEBANG LEAF (Coryphautan), POLYVINYL ALCOHOL ANDCITRIC ACID

Abstract: Cellulose extracted from gebang (Corypha utan) leaves was characterized and used as a raw material for preparation of carboxymethyl cellulose which further used for preparing a film. Carboxymethyl Cellulose/polyvinyl alcohol films were prepared by the crosslinking method. The films were chemically crosslinked with citric acid for tuning their properties.The results indicate that the hydrogen bond interactions between carboxymethylcellulose/polyvinyl alcohol and citric acid can be formed. The films demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…A maximum inhibition zone was recorded of 22 mm with 12 (wt%) CA against K. pneumoniae and 12 mm as the lowest measured inhibition zone with 10 (wt%) CA was applied against E. coli. These results are consistent with obtained results by Mahdavinia et al [33] and Siregar et al [34], who reported that CA crosslinked PVA-CMC films have powerful antimicrobial properties. These results could be attributed to citric acid possesses non dissociated form (-COOH) that can permeate the bacterial cell membrane, and allowing to donate hydrogen ions to the system.…”
Section: Antimicrobial Activitysupporting
confidence: 93%
“…A maximum inhibition zone was recorded of 22 mm with 12 (wt%) CA against K. pneumoniae and 12 mm as the lowest measured inhibition zone with 10 (wt%) CA was applied against E. coli. These results are consistent with obtained results by Mahdavinia et al [33] and Siregar et al [34], who reported that CA crosslinked PVA-CMC films have powerful antimicrobial properties. These results could be attributed to citric acid possesses non dissociated form (-COOH) that can permeate the bacterial cell membrane, and allowing to donate hydrogen ions to the system.…”
Section: Antimicrobial Activitysupporting
confidence: 93%
“…Overall, 2% xylan and modified xylan biofilms exhibited rough morphological surfaces as compared to 1% xylan and modified xylan biofilms. It was possibly due to difficulty for the large number of polymers to cross‐link with CA (Siregar et al ., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial activity of xylan biofilms was found to be less than that of CMX biofilms but more than that of AX biofilms as SEM images revealed that AX had great affinity to cross-link with CA. However, standard tetracycline showed larger ZOI than biofilms Siregar et al (2019). observed that CMC/PVA/CA films demonstrated antibacterial effects against Escherichia and Staphylococcus.…”
mentioning
confidence: 89%
“…Among the biopolymers used to prepare food packaging, carboxymethyl cellulose (CMC) has been widely used owing to its biodegradability, non-toxicity and low cost (Atta et al 2021a , b ). CMC can be blended with a biocompatible polymer such as polyvinyl alcohol (PVA) to enhance the physical and mechanical properties (Siregar et al 2019 ). Muppalla et al ( 2014 ) found that the incorporation of 4% citric acid into PVA/CMC/aloe vera film led to the formation of ester bonds resulting in 75% increase in tensile strength.…”
Section: Introductionmentioning
confidence: 99%